NEUROSCIENCE AND MATHEMATICAL EDUCATION: EXPLORING STUDENT BRAIN DEVELOPMENT AND TEACHING STRATEGIES - Adeilton de O. Andrade, Emanuel; Pessoa da Silva, Isaías; Aldeni de O. Andrade, Maria; de Assis de O. Andrade, Francisco (Journal of Interdisciplinary Debates, 2025)
This article explored how neuroscience knowledge can enrich pedagogical practice in teaching Mathematics, especially in the final years of Elementary School. The research problem investigated how neuroscience contributes to understanding brain development, students and to formulating effective pedagogical strategies. The study, conducted through a literature review, identified the brain areas involved in mathematical reasoning, analyzed the cognitive and emotional aspects of students and proposed pedagogical strategies based on neuroscientific evidence, such as immediate feedback, spaced repetition and gamification. The main conclusions indicate that the integration of neuroscience with mathematics education can improve student performance, promote engagement and create more welcoming and effective learning environments. The study suggests investments in teacher training and in the adaptation of neuroscientific approaches to different contexts, aiming to democratize access to innovative educational practices.